Analysis of Academic Psychological Capital of Guidance and Counseling Teachers Based on Length of Work - Harum, Akhmad (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2024)
This study aims to find out the difference Academic Psychological Capital based on the length of work working as a Guidance and counseling teacher in South Sulawesi. This quantitative descriptive study involved 334 guidance and counseling teachers in South Sulawesi.. Instruments used using Psychological Capital Questionnaire (PCQ) in accordance with the previous construction of PCQ developed by (Luthans, F., Youssef-Morgan, C. M., & Avolio, 2015) There are 24 statements prepared based on four aspects of psychological capital, namely self-efficacy, optimism, hope, and resilience. Data analysis using descriptive analysis and Anova. The results of the study show that There is a difference in academic Psychological Capital for BK teachers seen in the length of work under 10 years and above 10 years where in the aspects of hope and belief, resilience and optimism show that the longer people work and the duration above 10 years shows the higher the academic psychological capital and vice versa for someone who works under 10 years The level of academic psychological capital is lower